The Transparent Brain in Couple and Family Therapy : Mindful Integrations with Neuroscience - Hanna, Suzanne Midori, 1950-, author 342735 (New York, NY : Routledge, 2021)
"Bringing together clinical expertise with the latest findings from social, affective, and cognitive neuroscience, this accessible guide outlines how basic concepts of neuroscience and family therapy can be highly relevant to all mental health treatment. Written in a jargon-free style, The Transparent Brain in Couple and Family Therapy, second edition is an essential resource for mental health professionals using neuroscientific principles to bring relief to clients from diverse backgrounds"--